2017
DOI: 10.1111/dom.12871
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship of glycated haemoglobin and reported hypoglycaemia to cardiovascular outcomes in patients with type 2 diabetes and recent acute coronary syndrome events: The EXAMINE trial

Abstract: AimsTo investigate relationships between glycated haemoglobin (HbA1c) and reported hypoglycaemia and risk of major adverse cardiovascular events (MACE).MethodsThe EXAMINE trial randomized 5380 patients with type 2 diabetes (T2DM) and a recent acute coronary syndrome (ACS) event, in 49 countries, to double‐blind treatment with alogliptin or placebo in addition to standard of care. We used Cox proportional hazards models to analyse relationships among MACE, HbA1c levels and hypoglycaemic events.ResultsPatients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 14 publications
2
41
1
3
Order By: Relevance
“…Similarly, a nonsignificant increase in the risk for nonfatal stroke was observed in individuals those who had (hazard ratio 1.81, P = 0.085) versus those who had not experienced severe hypoglycemia. However, a recently published study using data from the Examination of Cardiovascular Outcomes with Alogliptin versus Standard of Care (EXAMINE) study observed that the adjusted hazard ratio for MACE risk in patients who experienced serious hypoglycemia events (hazard ratio 2.42, P = 0.007) was significantly higher than those without serious hypoglycemia exposure . However, this study did not report effects on nonfatal stroke separately.…”
Section: Incidence Of Hypoglycemia and The Risk Of Cerebrovascular Evmentioning
confidence: 79%
“…Similarly, a nonsignificant increase in the risk for nonfatal stroke was observed in individuals those who had (hazard ratio 1.81, P = 0.085) versus those who had not experienced severe hypoglycemia. However, a recently published study using data from the Examination of Cardiovascular Outcomes with Alogliptin versus Standard of Care (EXAMINE) study observed that the adjusted hazard ratio for MACE risk in patients who experienced serious hypoglycemia events (hazard ratio 2.42, P = 0.007) was significantly higher than those without serious hypoglycemia exposure . However, this study did not report effects on nonfatal stroke separately.…”
Section: Incidence Of Hypoglycemia and The Risk Of Cerebrovascular Evmentioning
confidence: 79%
“…Our analysis provides robust chronological evidence that death and CV events occur soon after a severe hypoglycaemic event. Few studies have investigated the temporal relationship between severe hypoglycaemia and CV events, as well as death, and most such studies were post‐hoc analyses of randomized controlled trials . Moreover, in these sub‐analyses, the credibility of results was limited by the small number of severe hypoglycaemic events and subsequent CV events.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there remains considerable controversy regarding the potential temporal relationship between severe hypoglycaemia and adverse cardiovascular events. In the Examination of Cardiovascular Outcomes with Alogliptin Versus Standard of Care (EXAMINE) trial, it was found that severe hypoglycaemia was associated with higher rates of major adverse cardiovascular events (MACE), but this did not reach a level of statistical significance if only MACE after a hypoglycaemic event was included in the analysis . Results from the Trial Comparing Cardiovascular Safety of Insulin Degludec Versus Insulin Glargine in Subjects With Type 2 Diabetes at High Risk of Cardiovascular Events (DEVOTE) showed a greater risk of all‐cause mortality in the short term after a severe hypoglycaemic episode and a decreased risk with long‐term windows, although there was a non‐significant association between severe hypoglycaemia and the risk of MACE .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CGM profiles provide far more information than just the mean glucose concentration by identifying patterns of hyperglycemia and hypoglycemia as well as potentially dangerous high or low glucose concentrations that are often missed with self-monitoring of blood glucose. The results of secondary analyses of two major studies (the Examination of Cardiovascular Outcomes with Alogliptin versus Standard of Care [EXAMINE] trial and the Atherosclerosis Risk in Communities [ARIC] Study) (25,26) that found an association between hypoglycemia and cardiovascular events emphasize the importance of understanding a patient’s glucose profile with CGM to potentially identify patients who may be at high risk for these events. Thus CGM by providing more clinical insights than HbA 1c or self-monitoring of blood glucose measurements can help optimize and personalize glucose control and diabetes management (27).…”
Section: Implications For Clinical Practicementioning
confidence: 99%